The Chemical Relationship Among Beta-Lactam Antibiotics and Potential Impacts on Reactivity and Decomposition - Turner, Jonathan; Muraoka, Alyssa; Bedenbaugh, Michael; Childress, Blaine; Pernot, Lauren; Wiencek, Mark; Peterson, Yuri K. (Frontiers in Microbiology, 2022)
ABSTRACT Beta-lactam antibiotics remain one of the most commonly-prescribed drug classes, but they are limited by their propensity to cause hypersensitivity reactions (e.g., from allergy to anaphylaxis) as well as by the emergence of bacteria with a myriad of resistance mechanisms such as β-lactamases. While development efforts continue to focus on overcoming resistance, there are ongoing concerns regarding cross-contamination of β-lactams during manufacturing and compounding of these drugs. Additionally, there is a need to reduce levels of drugs such as β-lactam antibiotics in waste-water to mitigate the risk of environmental exposure. To help address future development of effective remediation chemistries and processes, it is desired to better understand the structural relationship among the most common β-lactams. This study includes the creation of a class-wide structural ordering of the entire β-lactam series, including both United States Food and Drug Association (US-FDA)-approved drugs and experimental therapies. The result is a structural relational map: the “Lactamome”, which positions each substance according to architecture and chemical end-group. We utilized a novel method to compare the structural relationships of β-lactam antibiotics among the radial cladogram and describe the positioning with respect to efficacy, resistance to hydrolysis, reported hypersensitivity, and Woodward height. The resulting classification scheme may help with the development of broad-spectrum treatments that reduce the risk of occupational exposure and negative environmental impacts, assist practitioners with avoiding adverse patient reactions, and help direct future drug research.